طبيعة اللغة العربية - Nakida, Mamad Fajar; Sagala, Rumadani; Kesuma, Guntur Cahaya (Al-Zahra: Journal for Islamic and Arabic Studies, 2023)
The Arabic language is considered a global international language, so references and sources were used in arabic and this language is not taught just for religious language but this language is taught to find out the arabic texts or references and sources written in arabic and to understand them well as well as to understand the Qur’anic texts and the purified prophetic texts or in other words as it has circulated on the tongues of the majority of the people of Indonesia that the Arabic language is the religious language because most of the Indonesian society were muslims as they used in some of their traditions and the application of some of the teachings of their religion in the Arabic language such as invitations, prayers, dhikr, supplications, wirds and the like, because the Arabic language has unique natures, distinct and universal, as this language is characterized by special and unique natures that differ from other languages, and the universality of this language is evident in the availability of a set of common values between the Arabic language and other languages.